2020
DOI: 10.21203/rs.3.rs-18841/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protocol registration issues of systematic review and meta-analysis studies: a survey of global researchers

Abstract: Background: Although protocol registration of systematic reviews/meta-analysis (SR/MA) is still not mandatory, authors are strongly suggested to publish their SR/MA protocols prior to submitting their manuscripts for publication as recommended by the Cochrane guidelines for conducting SR/MAs. We aimed to assess awareness, obstacles, and opinions of SR/MA authors about the protocol registration process. Methods: A cross-sectional survey study included all authors who published SR/MAs during the period from 2010… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is generally acknowledged that all decision‐making should be made upon bias‐free evidence. Therefore, the tool requiring an MA should have a prior protocol and register it on public websites (e.g., PROSPERO), as a preregistered protocol can inform the process of conducting an MA, reduce duplicate efforts, and help identify selective reporting bias (Page et al, 2014; Tawfik et al, 2020). An empirical study (Zheng et al, 2021) revealed that the prospective registration of protocols was positively associated with methodological and reporting quality of systematic reviews on type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally acknowledged that all decision‐making should be made upon bias‐free evidence. Therefore, the tool requiring an MA should have a prior protocol and register it on public websites (e.g., PROSPERO), as a preregistered protocol can inform the process of conducting an MA, reduce duplicate efforts, and help identify selective reporting bias (Page et al, 2014; Tawfik et al, 2020). An empirical study (Zheng et al, 2021) revealed that the prospective registration of protocols was positively associated with methodological and reporting quality of systematic reviews on type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Third, only RCTs and CCTs, which are regarded as the highest level of evidence, were included in our quantitative analysis [109]. Moreover, prior protocol registration and subgroup analysis were also the strengths of the current meta-analysis [110,111]. Different root canal area, irrigation protocols, or intracanal medicament periods are potential factors affecting the heterogeneity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Third, only RCTs and CCTs, which are regarded as the highest level of evidence, were included in our quantitative analysis [111]. Moreover, prior protocol registration and subgroup analysis were also the strengths of the current meta-analysis [112,113]. Different root canal area, irrigation protocols, or intracanal medicament periods are potential factors affecting the heterogeneity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%